Determinants of PBB-P2 Taxpayer Compliance in Manding District - Elli Yana; Erna Sulistyowati (ACCOUNT: Jurnal Akuntansi, Keuangan dan Perbankan, 2026)
Local taxes represent a crucial source of funding for regional development, particularly through Land and Building Tax (PBB-P2). Therefore, the level of taxpayer compliance plays a significant role in determining whether tax revenue can be optimized. However, in practice, compliance levels remain relatively low. This is despite the theoretical expectation that factors such as taxpayer awareness, tax knowledge, and tax socialization can enhance compliance. This gap highlights a discrepancy between expected concepts and real-world conditions. This study aims to analyze the influence of taxpayer awareness, tax knowledge, and tax socialization on PBB-P2 taxpayer compliance in Manding District, Sumenep Regency. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents selected from a total population of 37,096 taxpayers using proportionate stratified random sampling. Data analysis was conducted using the PLS-SEM method with SmartPLS 4.0 software. The findings indicate that all three variables have a positive and significant effect on taxpayer compliance. The R-square value of 0.558 suggests that 55.8% of the variation in compliance can be explained by the model. These results reinforce the importance of internal factors in improving compliance, highlighting the need for continuous enhancement of tax education and socialization efforts. Keywords: Taxpayer Awareness, Tax Knowledge, Tax Socialization, Taxpayer Compliance.